Analisis Kinerja Keuangan dengan Menggunakan Metode Common Size pada PT. Holcim Indonesia Tbk - Riri Rifardi; R. Deni Muhammad Danial; Dicky Jhoansyah (COSTING : Journal of Economic, Business and Accounting, 2019)
Financial statements are used as a tool to find out how the financial performance of the company and can produce useful conclusions. This study aims to determine the financial performance of PT. Holcim Indonesia Tbk, which headlined the 2013-2017 balance sheet and income statement using the common size method. The research method applied in this study is to use descriptive research with a quantitative approach. The results of research conducted indicate the current assets of PT. Holcim Indonesia Tbk is not comparable with the short-term liabilities that are borne by the company, this shows the low liquidity of the company, from solvency, the company uses the capital on the assets of most of the liabilities owned, thus decreasing the level of company sovability and can make a low margin of safety for creditor. Judging from the income statement, it shows that the marketing strategy of the company is not good, as seen from the increase in cost of goods sold and making the gross profit margin decrease. For the company's ability to generate profits, the company's net profit margin from year to year has decreased to a loss in 2016-2017. This shows that financial performance has deteriorated because the company's profitability has always declined to the point of loss. Keywords: Financial Performance, Financial Statements, Common Size Method.